PEMANFAATAN TEPUNG TALAS DAN TEPUNG KACANG MERAH DALAM PEMBUATAN CRACKERS - MELIYANA MELIYANA; VONNY SETIARIES JOHAN; YELMIRA ZALFIATRI (Jurnal Sagu, 2019)
This research was aimed to get the best crackers from a combination ratio of taro flour and red bean flour incrackers making. Research method was completely randomized design (CRD) experiment which consisted offive treatments and each treatment was repeated three times. Treatments of taro flour and red bean flour were90:10, 80:20, 70:30, 60:40, 50:50. Data were statistically analyzed by using analysis of variance and continuedwith duncan’s new multiple range test at 5% level. The result of this study showed that the ratio of taro flourand red bean flour significantly affected moisture contents, ash contents, protein contents, color, flavour,aroma, and crunchiness. Based on this research, the best treatment was the crackers with taro flour and redbean flour 50:50, which had average of moisture content of 2.21%, ash content of 2.53%, and protein contentof 9.07%. Sensory assessment of crackers by panelist showed that this crackers had a brown color, red beantaste, red bean flour, and rather hard textures.